Integrating Waqf-Based Forests and Carbon Trading: Opportunities, Challenges, and Strategies in Indonesia - Ali, Khalifah Muhamad; Tanjung, Hendri; Sukmana, Raditya; Jannah, Miftahul; Mustaqimah, Mu'minah (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Carbon trading is pivotal in mitigating greenhouse gas emissions. However, the contribution of waqf-based forests—forests established on endowed land—remains underexplored. This research addresses this gap by investigating the potential, schemes, stakeholders, opportunities, challenges, and strategies for waqf-based forests in carbon trading. Through a literature review, in-depth interviews, and field observations, the study found that waqf-based forests can contribute to carbon trading and raise Islamic awareness. The findings identify two potential schemes for selling carbon credits from waqf-based forests: the Ministry of Environment and Forestry’s carbon exchange and direct business-to-business (B2B) transactions. Due to the sustainability of waqf land and its added ecological, economic, social, and Islamic values, waqf-based forests can produce high-quality carbon credits and provide an inclusive and sustainable green economy. However, challenges such as suboptimal land area, lack of technical knowledge, and the absence of a carbon trading fatwa need to be addressed. Proposed strategies to overcome these challenges include document bundling, collaborations with Corporate Social Responsibility (CSR) programs, direct B2B sales, and selecting plants that enhance carbon economic value. This research offers in-depth insights into the potential of waqf-based forests as significant players in carbon trading, emphasizing their inherent sustainability values. Keywords: carbon trading, green economy, high-quality carbon credit, waqf-based forest